2017
DOI: 10.4236/ajac.2017.88038
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight in the Physical and Photoelectrochemical Properties of Molybdenum Disulfide Alpha-Hematite Nanocomposite Films

Abstract: The alpha (α)-hematite (Fe 2 O 3 ) as photoanode has been used for photoelectrochemical applications due to low bandgap, low cost, high chemical stability, nontoxicity, and abundance in nature. The doping with various transition metals, formation of nanostructured and nanocomposite of α-Fe 2 O 3 have been attempted to enrich the carrier mobility, surface kinetics and carrier diffusion properties. The manuscript is an attempt to improve the photoelectrochemical properties of α-Fe 2 O 3 by formation of nanocompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The effective surface area was calculated to be 0.045 and 0.055 cm 2 for 2H and 1T MoS 2 nanoflakes respectively using the Randles Sevcik equation. 51 It is obvious that even though there isn't much increase in peak currents (Ip), the cathodic (Ipc) and anodic (Ipa) peak current are found to increase with increasing scan rate exhibiting a linear proportion between the redox peak currents and square root of scan rate. It can be suggested that, apart from surface area, the enhanced catalytic activity is contributed from the metallic phase and electroactive edge sites of 1T-MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The effective surface area was calculated to be 0.045 and 0.055 cm 2 for 2H and 1T MoS 2 nanoflakes respectively using the Randles Sevcik equation. 51 It is obvious that even though there isn't much increase in peak currents (Ip), the cathodic (Ipc) and anodic (Ipa) peak current are found to increase with increasing scan rate exhibiting a linear proportion between the redox peak currents and square root of scan rate. It can be suggested that, apart from surface area, the enhanced catalytic activity is contributed from the metallic phase and electroactive edge sites of 1T-MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Several nanostructures of these oxides such as nanowires, nanotubes, nanoparticles, and nanoflowers, have been recently studied. Among these structures, hierarchical nanostructures have emerged as one of the most popular nanostructures owing to their enhanced light absorption, interfacial charge transfer, electrolyte penetration, and high surface‐to‐volume ratio properties [164–166] . However, the photocatalytic activity of these nanostructured materials is limited by photo corrosion and rapid charge recombination.…”
Section: Hierarchical Nanostructures For Solar Energy Applicationsmentioning
confidence: 99%
“…Among these structures, hierarchical nanostructures have emerged as one of the most popular nanostructures owing to their enhanced light absorption, interfacial charge transfer, electrolyte penetration, and high surface-to-volume ratio properties. [164][165][166] However, the photocatalytic activity of these nanostructured materials is limited by photo corrosion and rapid charge recombination. Therefore, these inadequacies have motivated researchers to fabricate hierarchical nanostructurebased heterojunctions for efficient water splitting.…”
Section: Structural and Pec Characteristicsmentioning
confidence: 99%